Systematic overview of neuroanatomical differences in ADHD: Definitive evidence. Issue 1 (2nd January 2018) - Vieira de Melo, Bruno Bastos; Trigueiro, Maria João; Rodrigues, Pedro Pereira
ABSTRACT: Objectives : This article seeks to identify neuroanatomical differences in ADHD through an overview of systematic reviews that report encephalic differences compared to a control group in volume, area, activation likelihood or chemical composition. Methods : We conducted a systematic search using Cochrane guidelines and PRISMA criteria in PubMed, Scopus, Web of Science, Cochrane Database of Systematic Reviews and Database of Abstracts of Reviews of Effects. Results : Results revealed broad encephalic involvement that includes a functional frontal and cingulate hypoactivation and structural differences in corpus callosum, cerebellum and basal nuclei. Conclusions : ADHD symptoms might be due to a multi-network unbalanced functioning hypothesis.